Neo-Pentecostalism and gender-based violence before and during COVID-19 in South Africa - Shingange, Themba (In die skriflig : tydskrif van die Gereformeerde Teologiese Vereniging, 2023)
Pentecostal Christians in Africa preach a pragmatic gospel that attempts to address social, practical and contextual concerns. Similar patterns may be seen in the emergence of neo-Pentecostalism in South Africa and other parts of the continent. Neo-Pentecostalism is commonly known for the use of God-talk that promises people solutions to their socio-economic issues such as unemployment and poverty if they obey the prescripts of the so-called ‘prophets’ or ‘man of God’. Nonetheless, the global devastation caused by the COVID-19 left much to be desired. In South Africa, it highlighted the high extent of gender-based violence (GBV) in addition to other societal issues. Although GBV has always been a problem in South Africa, its cases increased drastically during the COVID-19 pandemic to the point where GBV was also declared a pandemic. This has compelled various social structures to start exploring solutions to stop this conundrum. The overarching question posed in this article was how neo-Pentecostal rhetoric about God contributes to GBV cases in South Africa before and during the COVID-19 pandemic, given that God-talk has been utilised to influence people’s perceptions of and reactions to other societal concerns. As a result, this article aimed to investigate this subject while also outlining some potential solutions that African Pentecostals can consider as possible contributions to the struggle against GBV in contemporary South Africa. The study used a literature analysis to achieve this goal and it followed an interdisciplinary approach in the collection of the relevant data. These disciplines included theology, social sciences gender and sexuality studies. Therefore, the literature analysis focused on how neo-Pentecostalism intersect with gender and social issues that are actors in the rise of GBV in South Africa. Furthermore, the concept of God-talk was adopted as a theoretical framework guiding the discussion in this article, whilst the African ethic of Ubuntu [humanness] was proposed as an antidote that can be used in transforming God-talk and contributors of GBV in church and society. Ubuntu brings to consciousness that pastors and every member of society should treat each other as created in the image of God and with respect and humanness as we all exist because of and for others.ContributionsThis article contributes to the body of knowledge aimed at finding solutions to GBV in South Africa. Finding solutions is critical as GBV continue to be a challenge in South Africa and elsewhere.